Micromilling performance analysis – cold air assisted aluminium machining behaviour observation - Nurul Hasya, Md. Kamil; Mohd Nizar, Mhd Razali; Ahmad Shahir, Jamaludin; Siti Nadiah, Mohd Saffe; Musfirah, Abdul Hadi (Institution of Engineering and Technology, 2022)
The primary goal of this work is to investigate the performance of micro mill tools in terms of tool wear, average surface roughness, and chip size when machining aluminium alloy, as well as to evaluate the effect of cutting fluid application, using a 0.9 mm tungsten carbide (WC) tool with two flutes. This is because it is recognized that one of the essential factors in the micro-cutting process is the micro-cutting tool itself. The tool failure or wear affects the cost, average surface roughness, functionality, and the quality of the finished product greatly. The research is conducted under different cutting conditions with a varying feed rate of 0.001mm/tooth to 0.005mm/tooth and a cutting speed of 3.142m/min to 9.425m/min using a side milling process where the side flank face wear progression of the tool is measured. Then, the average surface roughness and chip size data are collected using a 3D laser measurement microscope. Based on the results, there is a similar tool wear trend in the micro-cutting process with the conventional methods. The results show that the use of cutting fluid has a significant impact on the quality of machined parts, both in terms of burr formation and machined surface quality. The relative size of the burrs formed is much larger than in macro machining operations, depending on the cutting conditions. Tool life and surface finish are impacted by built-up edges on cutting tools. The premature tool failure of the dry condition micro-cutting process is often focused on the entrance of the work-piece. Other than that, it is found that there are some instances where the average surface rough-ness decreases abruptly when it is reaching the fracture zone which is caused by the geometrical effect from the worn edge of the tool. This could be applied in the future design of the micro tool suitable for high-speed machining in dry conditions. It is also concluded that an appropriate selection of machining conditions has the potential to reduce tool wear rate and encourages longer tool life.